Dynamic Visual Landscape Assessment of Disused Railway in Complex Terrain: A Study of Jingmen Railway - Yueyi Wang; Shaohua Wang; Xin Wang; Xiaoyu Huang; Xiao Li; Xueyan Zhang; Ziqiong Li (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Against the backdrop of the partially idle resources of conventional railways and the continuous growth of suburban leisure tourism demand, it is required to develop railway tourism by utilizing the disused resources of conventional railways in China. Therefore, restoring, analyzing, and evaluating the visual landscapes seen when traveling on conventional trains are extremely important. The innovation of this study is proposing a dynamic visual landscape interface for disused railways, which establishes a connection between the “seeing” and “perceiving” for passengers and describes the visual landscape they observe. By analyzing the dynamic visual factors of passengers and combining DEM data, the temporal-spatial relationship of the visual landscapes along the railway is described as a dynamic visual landscape interface model. Based on this, the study proposes criteria and indicators for analyzing and evaluating the dynamic visual landscapes of railways, using typical landscapes along the Jingmen railway as an example for evaluation and validation. The research results provide analytical and decision-making tools for repurposing disused railways as tourist railways.